2016
DOI: 10.20960/nh.239
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year trends (2000-2010) in bias of self-reported weight, height and body mass index in a Mediterranean adult population

Abstract: Aim: To assess trends in the biases of self-reported versus measured weight, height, and body mass index (BMI) in adults over the period 2000-2010 in a Mediterranean adult population.Methods: The sample population consisted of young (18-35) and middle-aged (36-55) adults living in the Balearic Islands, Spain. The data represent 1,089 people during 1999-2000 and 1,081 people during 2000-2010. Weighted-based frequency estimates were used.Results: While no differences between self-reported and measured weight, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The observed self-report bias in these anthropometric characteristics was consistent with reports from previous research with different participant samples, confirming a general human tendency to overestimate height and -Gortari et al, 2007;Bes-Rastrollo et al, 2005;Bibiloni et al, 2016). The marathon runners' self-report bias for body mass ($0.6 kg), BMI ($0.35 kg Á m À2 ), and height ($0.4 cm) observed in this study was consistent with a previous study of athletes that reported an underestimate of BMI calculations by 0.4 kg Á m À2 (Knechtle et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The observed self-report bias in these anthropometric characteristics was consistent with reports from previous research with different participant samples, confirming a general human tendency to overestimate height and -Gortari et al, 2007;Bes-Rastrollo et al, 2005;Bibiloni et al, 2016). The marathon runners' self-report bias for body mass ($0.6 kg), BMI ($0.35 kg Á m À2 ), and height ($0.4 cm) observed in this study was consistent with a previous study of athletes that reported an underestimate of BMI calculations by 0.4 kg Á m À2 (Knechtle et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…There is a debate on BMI for the detection of excess weight (Ramos-Silva, Savegnago-Mialich, Hoffman & Jordao, 2017), but findings supports its utility (Doménech-Asensi et al, 2018). In addition, no differences have been found between selfreported and measured weight, height and BMI (Bibiloni et al, 2016). Moreover, like in other studies (Benton & Karazsia, 2015), an online survey was used to collect the data, so it is possible that only those individuals with economic or educational resources allowing access to it or those highly motivated to collaborate in this type of studies might have participated.…”
Section: Discussionmentioning
confidence: 99%